2013
DOI: 10.14419/ijbas.v2i3.922
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Pulp black liquor waste as a cement admixture

Abstract: The pulp black liquor waste (PBL), a byproduct from paper-making, is applied as a cement admixture in two types of cement, namely Ordinary Portland cement (OPC) and Portland limestone cement (LPC). The results showed that the water of consistency of cement pastes premixed with PBL was gradually increased with the concentration of PBL while the setting times (initial and final) were decreased. So, it can be used as an accelerator. The compressive strength increased slightly during the early ages of hydration bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…A similar work on the stabilization of ceramic particles using anionic polymeric dispersants, it was reported that the addition of poly acrylic acid and poly ethylene glycol improved the dispersion of ceramic particles in the suspension [54]. In addition, the produced carboxymethylated lignin may also be used as a dispersant in the mining industry (ore suspensions), pesticide formulations, ceramic suspensions and cement admixture [14,17,[55][56] …”
Section: Impacts Of Ph and Concentration On Solubilitymentioning
confidence: 92%
“…A similar work on the stabilization of ceramic particles using anionic polymeric dispersants, it was reported that the addition of poly acrylic acid and poly ethylene glycol improved the dispersion of ceramic particles in the suspension [54]. In addition, the produced carboxymethylated lignin may also be used as a dispersant in the mining industry (ore suspensions), pesticide formulations, ceramic suspensions and cement admixture [14,17,[55][56] …”
Section: Impacts Of Ph and Concentration On Solubilitymentioning
confidence: 92%
“…According to studies by a number of scientists (Kanaev et al, 2016), (Bekebaeva et al, 2019), it was found that the tailings from enrichment, located in the tailings have the following chemical and mineralogical composition, given in Table 1. From the chemical composition of waste from enrichment, we can see that their chemical composition contains a number of useful compounds, in particular, oxides of silicon, aluminum, and iron, as well as residual compounds of lead and zinc, which in terms of ecology and human life safety are heavy nonferrous metals, which have a negative anthropogenic impact on the environment and public health, but at the same time, they are one of the valuable non-ferrous metals for the metallurgical industry (Kalmakhan, 2022), (Аyeni et al, 2012), (Kolesnikov et al, 2022), (Chen et al, 2011), (Zhanikulov et al, 2022), (Choudhary et al, 2013), (Darweesh et al, 2014), (Zhanikulov et al, 2021) and can be used as secondary raw materials in a number of industries, such as metallurgy and chemical technology.…”
Section: исследования отходов горно-металлургической промышленности с...mentioning
confidence: 99%
“…Most of the plant residues are waste biomass On this basis, sugarcane bagasse residues are one of these biomasses. When lignin and cellulose could be separated from this waste using a low pressure and ecofriendly method, the lignin might be then able to be converted to a sustainable bio-product, which it successfully could be used in cement as an admixture [9,10]. The deep eutectic solvents are considered to be deconstructing waste biomasses having the potential to be technically and economically a viable alternative to volatile organic solvents [10][11][12][13][14][15].…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…The increase of bulk density and the decrease of total porosity are due to many reasons as the normal hydration of cement phases [31,32], the activation response of lignin to cement phases [7,9,14,38], the filling effect of lignin [9,14,39], and moreover the dispersive influence of lignin and the improving of workability of the cement pastes [20,28,34,36,40]. The decrease of bulk density and the increase of total porosity are due to the decrease of the rate of hydration resulting from the higher increase of lignin content, which are often standing as an obstacle that hindered the rate of the normal hydration because this makes for the cement particles to be apart from each other, and therefore the rate of hydration is adversely affected [41][42][43].…”
Section: Day 3 Days 7 Days 28 Days 90 Daysmentioning
confidence: 99%
See 1 more Smart Citation